FEATURES OF BONE METABOLISM IN PATIENTS WITH DIABETIC OSTEOARTHROPATHY OF VARIOUS STAGES - Kamalov T. T; Tadjibayev S. S. (International Engineering Journal For Research & Development, 2022)
In this article, the authors studied the features of bone metabolism in 67 patients with type 2 diabetes and with diabetic osteoarthropathy of various stages. The levels of 25-hydroxyvitamin D 3 were significantly lower in patients of all 4 x groups (average age 70 ± 12 years) than in the control group (27.2 ± 6.2 ng / ml). It should be noted that 34 (50.7%) of patients with diabetic pope ulcers had a severe deficiency of 25-hydroxyvitamin D 3 with levels below 10 ng / ml. Only 13% of patients, the level of 25-hydroxyvitamin D 3 exceeded 20 ng / ml. In addition, secondary hyperparathyroidism was found in 26% of patients, and at 12.5% of patients a hypocalcemia was revealed. A negative correlation was established (R = -0.241) (p <00,1) between the classification of Armstrong and the status of 25-hydroxyvitamin D 3. The authors concluded that patients with diabetic foot syndrome complicated by Stop Charcot are susceptible to high risk of 25-hydroxyvitamin d3 and calcium deficiency. Any patient with the diabetic foot syndrome should take measurement of the level of 25-hydroxyvitamin D 3 and obtain prophylactic treatment when reduced indicators are detected.